Nanoscale mineralization of cell-laden methacrylated gelatin hydrogels using calcium carbonate–calcium citrate core–shell microparticles. Issue 46 (15th November 2021) - Subbiah, Ramesh; Balbinot, Gabriela de Souza; Athirasala, Avathamsa; Collares, Fabricio Mezzomo; Sereda, Grigoriy; Bertassoni, Luiz E.
Abstract : Bone-like scaffolds were developed using a facile microparticles-assisted nanoscale mineralization of human mesenchymal stem cell-laden hydrogels. Abstract : Conventional biomaterials developed for bone regeneration fail to fully recapitulate the nanoscale structural organization and complex composition of the native bone microenvironment. Therefore, despite promoting osteogenic differentiation of stem cells, they fall short of providing the structural, biochemical, and mechanical stimuli necessary to drive osteogenesis for bone regeneration and function. To address this, we have recently developed a novel strategy to engineer bone-like tissue using a biomimetic approach to achieve rapid and controlled nanoscale mineralization of a cell-laden matrix in the presence of osteopontin, a non-collagenous protein, and a supersaturated solution of calcium and phosphate medium. Here, we build on this approach to engineer bone regeneration scaffolds comprising methacrylated gelatin (GelMA) hydrogels incorporated with calcium citrate core–shell microparticles as a sustained and reliable source of calcium ions for in situ mineralization. We demonstrate successful biomineralization of GelMA hydrogels by embedded calcium carbonate–calcium citrate core–shell microparticles with the resultant mineral chemistry, structure, and organization reminiscent of that of native bone. The biomimetic mineralization was further shown to promote osteogenic differentiation of encapsulated human mesenchymal stem cells even in the absence of other exogenous osteogenic induction factors. Ultimately, by combining the superior biological response engendered by biomimetic mineralization with the intrinsic tissue engineering advantages offered by GelMA, such as biocompatibility, biodegradability, and printability, we envision that our system offers great potential for bone regeneration efforts.